Optical and Optoelectronic Studies of Binary and Ternary Films of Poly(L-Tryptophane), Poly(5-hydroxy-L-tryptophane), and P(TER-CO-TRI) Doped with Sudan Dye - Rahim, Barham K.; Amin, Peshawa O.; Muhammadsharif, Fahmi F.; Saeed , Salah R.; Ketuly, Kamal A. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2023)
In this work, the optical properties and optoelectronics parameters of binary and ternary composite films made of two electron acceptors, poly(L-Tryptophane) and poly(5-hydroxy-L-Tryptophane), with an electron donor, P(TER-CO-TRI), doped with Sudan dyes, are comprehensively investigated. The films with different volumetric ratios of the components were deposited onto the glass substrates using spin coating technique. Results showed that with the help of dye doping into the binary systems of poly(L-Tryptophane):P(TRI-co-TER) (1:2) and poly(5-hydroxy-L-Tryptophane):P(TRI-co-TER)(1:2), the refractive index was increased from 2.01 to 2.32. The nature of the electronic transition in the studied films was found to be a direct allowed transition, which was derived from Tauc’s equation. The combination of Cyclic voltammetry (CV) technique and absorption spectroscopy was used to determine the molecular energy levels, HOMO and LUMO of the polymer samples. It was seen that the mixture of poly(L-Tryptophane):P(TRI-co-TER):Sudan dye (1:2:2) has led to increase the energy gap to 2.95 eV and the real optical conductivity ( ) to about 433.11 S.cm-1. According to the findings, the investigated polymers can have a great potential for semitransparent organic solar cells.